Komunikasi Interpersonal Pelatih dan Pemain Basket Mountain Gold Timika Dalam Membangun Motivasi Untuk Meningkatkan Prestasi - Kosegeran, Brando; Trijayanto, Danang (LUGAS Jurnal Komunikasi, 2024)
Humans are social creatures that cannot be separated from socialization activities carried out through interactions with others. One of the activities carried out is communication. Basketball is an example of a big ball sport that requires interpersonal communication. This study aims to determine the Interpersonal Communication used by coaches in motivating basketball athletes Mountain Gold Timika so that their students in building quality so that their abilities become an achievement. The type of research used is qualitative. This research uses an interactive analysis model, which after the data collection process, data reduction, data presentation and conclusion drawing. Based on research that has been conducted by researchers regarding "Interpersonal Communication of Mountain Gold Basketball Coaches and Players in Building Motivation and Achievement", researchers can draw conclusions that interpersonal communication can help coaches in training and developing the achievements of Mountain Gold Timika basketball players.